La idoneidad didáctica en la formación de profesores de matemáticas - Font, Vicenç (2021)
In this workshop, first, an activity is presented with the purpose of knowing the aspects that the participants consider relevant to implement it in their classes; second, current trends in the teaching of mathematics are discussed, which allow giving a first answer to what is understood by the improvement of a teaching and learning process of mathematics and which have been used by the participants. In a third moment, the question "How should a suitable mathematics class be?" is deepened and the criteria of didactic suitability, with its components and indicators, are introduced as an answer to this question. Finally, tasks that have been used in teacher training to introduce some of these criteria and components are discussed.